Learning of Intimate Area Examination Amongst Pakistani Medical Students: KAP Study - Bakhtiari, Masooma; Ijaz, Muhammad Tayyab; Farooq, Rana Muhammad Umar; Daula, Muhammad Imran Hameed; Shahab, Amna (International Journal of Medical Students, 2023)
BACKGROUND: Intimate area examination (IAE) is an integral part of clinical examination skills and must be mastered by medical students before they start their careers. This study explores the experiences of Pakistani medical students regarding learning of IAE, the associated barriers and their impacts on students’ learning. METHODS: This cross-sectional study, based on a self-designed questionnaire was conducted at two Pakistani medical colleges which included final year students, and post graduate trainees. RESULTS: During their undergraduate training, 74.9% of the respondents had not conducted a female pelvic examination, 51.9% had not examined a female groin, 79.7% had not examined a female rectum and 72.7% had not examined a male rectum. From the 65 postgraduate doctors, 48.4% reported that they were not prepared to perform an IAE at the start of their clinical career. Regarding barriers to IAE learning more than half of the respondents felt that the opposite gender of the patient (64.7%) and patient’s refusal (63.1%) had a strong negative impact on IAE learning. A high percentage of respondents reported that they were not taught IAE during their undergraduate years. Among the currently used pedagogical techniques, 71.1% of the respondents opted for real patient-based learning, followed by clinical simulations (21.9%), and videos (7.0%). No one thought examination should be taught theoretically. A significant difference between male and female experience in IAE learning was also observed. CONCLUSION: Learning of IAE remains unsatisfactory and poses a major challenge for the Pakistani Medical Students in the institutes included in this study.